Influenza Neuraminidase Subtype N1: Immunobiological Properties and Functional Assays for Specific Antibody Response. - Don Changsom; Hatairat Lerdsamran; Witthawat Wiriyarat; Warunya Chakritbudsabong; Bunpote Siridechadilok; Jarunee Prasertsopon; Pirom Noisumdaeng; Wanibtisam Masamae; Pilaipan Puthavathana (PLoS ONE, 2016)
Influenza neuraminidase (NA) proteins expressed in TK- cells infected with recombinant vaccinia virus carrying NA gene of highly pathogenic avian influenza H5N1 virus or 2009 pandemic H1N1 (H1N1pdm) virus were characterized for their biological properties, i.e., cell localization, molecular weight (MW), glycosylation and sialidase activity. Immune sera collected from BALB/c mice immunized with these recombinant viruses were assayed for binding and functional activities of anti-NA antibodies. Recombinant NA proteins were found localized in cytoplasm and cytoplasmic membrane of the infected cells. H1N1pdm NA protein had MW at about 75 kDa while it was 55 kDa for H5N1 NA protein. Hyperglycosylation was more pronounced in H1N1pdm NA compared to H5N1 NA according to N-glycosidase F treatment. Three dimensional structures also predicted that H1N1 NA globular head contained 4 and that of H5N1 contained 2 potential glycosylation sites. H5N1 NA protein had higher sialidase activity than H1N1pdm NA protein as measured by both MUNANA-based assay and fetuin-based enzyme-linked lectin assay (ELLA). Plaque reduction assay demonstrated that anti-NA antibody could reduce number of plaques and plaque size through inhibiting virus release, not virus entry. Assay for neuraminidase-inhibition (NI) antibody by ELLA showed specific and cross reactivity between H5N1 NA and H1N1pdm NA protein derived from reverse genetic viruses or wild type viruses. In contrast, replication-inhibition assay in MDCK cells showed that anti-H1N1 NA antibody moderately inhibited viruses with homologous NA gene only, while anti-H5N1 NA antibody modestly inhibited the replication of viruses containing homologous NA gene and NA gene derived from H1N1pdm virus. Anti-H1N1 NA antibody showed higher titers of inhibiting virus replication than anti-H5N1 NA antibody, which are consistent with the results on reduction in plaque numbers and sizes as well as in inhibiting NA enzymatic activity. No assay showed cross reactivity with reassorted PR8 (H1N1) virus and H3N2 wild type viruses.